2022
DOI: 10.1093/biolre/ioac174
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α is essential for the augmentation of myometrial contractility during labor

Abstract: Uterine contraction is crucial for a successful labor and the prevention of postpartum hemorrhage. It is enhanced by hypoxia; however, its underlying mechanisms are yet to be elucidated. In this study, transcriptomes revealed that hypoxia-inducible factor (HIF)-1α was up-regulated in laboring myometrial biopsies, while blockade of HIF-1α decreased the contractility of the myometrium and myocytes in vitro via siRNA and the inhibitor, 2-methoxyestradiol. Chromatin immunoprecipitation sequencing revealed that HIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The cell contraction data confirmed that high glucose induced myometrium hypoxia and decreased contractility through TREK1. Interestingly, a recent study (54) reported that hypoxia and increased HIF-1a expression promote the contraction of myometrial and smooth muscle cells. These findings contradict our experimental results; however, we found some inconsistencies in the supplement Figure 4 of their paper and the conclusion about the cell contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The cell contraction data confirmed that high glucose induced myometrium hypoxia and decreased contractility through TREK1. Interestingly, a recent study (54) reported that hypoxia and increased HIF-1a expression promote the contraction of myometrial and smooth muscle cells. These findings contradict our experimental results; however, we found some inconsistencies in the supplement Figure 4 of their paper and the conclusion about the cell contraction.…”
Section: Discussionmentioning
confidence: 99%
“…With the progress of technologies, H Liu's group also published a series of papers in Frontiers using transcriptome sequencing (RNA-seq), mass spectrometry detection of proteome (LC-MS/ MS), single cell transcription sequencing (scRNA-seq), and spatial transcription (ST). In addition, they verified the involvement of inflammation and hypoxia in laboring myometrium and that gives some important hints for future studies (4)(5)(6).…”
mentioning
confidence: 60%
“…SMCs were cultured as per the previous description. 80 The contractility of SMCs was evaluated by a cell contraction kit (CBA‐201, Cell Biolabs Inc.) according to the manufacturer's instructions. The collagen preparation solution was diluted and mixed with cell suspension, then add to a 24‐well plate for 1 h culture to form solid gel, then add 1 ml medium continue to culture for 48 h. The SMCs were treated with contractile inhibitor (Biacetyl monoxime Diacetyl Monoxime, BPM) (10 μM) to inhibit constriction.…”
Section: Methodsmentioning
confidence: 99%
“…SMCs were cultured as per the previous description 80 . The contractility of SMCs was evaluated by a cell contraction kit (CBA‐201, Cell Biolabs Inc.) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%